Assessing burnout among health care professionals in a tertiary hospital in Kohalpur, Nepal: a cross-sectional study - Shah, Gaurav Jung; Shah Singh, Priyadarshini (Journal of Karnali Academy of Health Sciences, 2025)
Background: Burnout is a commonly observed psychological phenomenon that occurs due to prolonged stressors at work, which poses a risk to the health of the working population. Low patient care and safety are due to burnout in healthcare professionals, which could hamper their personal lives and quality. This study aims to find the prevalence of burnout and compare the three components of risk of burnout: emotional exhaustion, depersonalization and personal achievement. Methods: A cross-sectional study was conducted in a tertiary care hospital in Kohalpur, taking 196 healthcare professionals comprising of doctors and nurses, who met the inclusion criteria. Strata were developed based on the profession (doctors and nurses) and then using the probability sampling technique data was collected via Google Forms using the Maslach Burnout Inventory questionnaire. Results: This study depicted burnout in 9.7% of the participants (doctors 10.6% and 9.6% nurses), 5.23% higher in the surgery department and younger age group (10.6%). For the establishment of burnout there need to be high levels of emotional exhaustion (14.8%) and/or depersonalization (22.4%) and/or low levels of personal achievement (12.20%). A statistically significant association was found between emotional weariness in females, higher average working hours (> 8 hours), and a particular profession (nurses versus doctors). Personal success was statistically associated with age and years of work experience, while depersonalization was statistically significantly correlated with profession. The average number of hours worked per day was strongly associated with both emotional tiredness and personal achievement. Conclusion: The prevalence of burnout using the Maslach Burnout Inventory showed low risk of burnout, defined by, low levels of emotional exhaustion and depersonalization and high levels of personal achievement in the healthcare professionals working in a tertiary care hospital. The main sources of burnout included increased average working hours (>8 hours), decreased work experience (1- 5 years) and decreased age (20-30 years).